Shamans/neo-Shamans : ecstasy, alternative archaeologies, and contemporary pagans - Wallis, Robert J. (Routledge, 2003)
Shamans and shamanisms are in vogue at present. In popular culture, such diverse characters as occultist Aleister Crowley, Doors musician Jim Morrison and performance artist Joseph Beuys have been termed shamans. The anthropological construct 'shamanism', on the other hand, has associations with sorcery, witchcraft and healing, and archaeologists have suggested the meaning of prehistoric cave art lies with shamans and altered consciousness. Robert J. Wallis explores the interface between 'new' (modern western), indigenous and prehistoric shamans, and assesses the implications for archaeologists, anthropologists, indigenous communities, heritage managers, and neo-Shamanic practitioners. Identifying key figures in neo-Shamanisms, including Mircea Eliade, Carlos Castaneda and Michael Harner, Wallis assesses the way in which 'traditional' practices have been transformed into 'western' ones, such as Castaneda's Don Juan teachings and Harner's core shamanism. The book draws on interviews and self-reflective insider ethnography with a variety of practitioners, particularly contemporary pagans in Britain and north America from druid and heathen traditions, to elucidate what shamans do.; Wallis looks at historical and archaeological sources to elucidate whether 'Celtic' and 'northern' shamanism may have existed; he explores contemporary pagan engagements with prehistoric sacred sites such as Stonehenge and Avebury, and discusses the controversial use by neo-Shamans of indigenous (particularly native American) shamanism. Rather than discuss neo-Shamans as inauthentic, invalid culture-stealers, Wallis offers a more detailed and complex appraisal. He makes it clear that scholars must be prepared to give up some of their hold over knowledge, and not only be aware of these neo-Shamanic approaches but also engage in a serious dialogue with such 'alternative' histories.